A Spatiotemporal Analysis of Organic Pollutants Contamination in Ciliwung River, Indonesia - Pratama, Mochamad Adhiraga; Constantine, Dorothy Marsha (CSID Journal of Infrastructure Development, 2023)
Ciliwung River is one of many rivers on Java Island which is polluted by waste from domestic, commercial/industrial, and agricultural activities. The rapid population growth caused changes in land use. Along with population growth and the development of human activities in various sectors, river pollution became a serious problem for humans. The purpose of this study is to conduct a spatiotemporal analysis of the concentration of pollutant in Ciliwung River and its correlation with the trend of land use changes to determine the factors that dominantly influence river pollution. The analysis was carried out on the parameters of organic pollutants (BOD, COD, DO, and TSS) using the flow and water quality data of the Ciliwung River from BBWS Ciliwung – Cisadane. Spatially, the concentration of organic pollutants increased from upstream to downstream. Meanwhile, temporally, the concentration of organic pollutants (BOD and COD) peaked in 2018 and then decreased until 2020. From the trend of land cover changes and the value of coefficient correlation, an increasing percentage of residential land caused an increasing pollutant load, indicated by a moderate-strong positive correlation test between those two variables.